Identification of microRNA editing sites in three subtypes of leukemia - Xie, Wenping; Yang, Jun; Zhou, Nan; Ding, Hao; Zhou, Guangchen; Wu, Shuai; Guo, Shiyong; Li, Wanran; Zhang, Lei; Yang, Huaide; Mao, Chunyi; Zheng, Yun (Frontiers in Molecular Biosciences, 2022)
Leukemia is an aberrant hyper-proliferation of immature blood cells that do not form solid tumors. The transcriptomes of microRNAs (miRNAs) of leukemia have been intensively explored. However, miRNA editing of leukemia has not been extensively studied. To identify miRNA editing patterns and explore their functional relevance in leukemia, we analyzed 200 small RNA sequencing profiles of three subtypes of leukemia and identified hundreds of miRNA editing sites in three subtypes of leukemia. Then, we compared the editing levels of identified miRNA editing sites in leukemia and normal controls. Many miRNAs were differential edited in different subtypes of leukemia. We also found the editing levels of 3′-A editing sites of hsa-mir-21-5p and hsa-mir-155-5p decreased in chronic lymphocytic leukemia patients with radiation treatments. By integrating PAR-CLIP sequencing profiles, we predicted the targets of original and edited miRNAs. One of the edited miRNA, hsa-let-7b_5c, with an additional cytosine at 5′ end of hsa-let-7b-5p, potentially targeted VBP1 and CTDSP1. CTDSP1 was significantly downregulated in T-ALL compared to normal controls, which might be originated from the hyperediting of hsa-let-7b-5p in T-ALL. Our study provides a comprehensive view of miRNA editing in three different subtypes of leukemia.